MUDIK LEBARAN DAN PERTUMBUHAN EKONOMI DALAM PERSPEKTIF KAIDAH AL-‘ADAH MUHAKKAMAH - Zulkifli, Zulkifli; Nurmala, Putri; Arrahmah, Siti (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
This study aims to determine how Lebaran homecoming as an economic context in the perspective of al-‘adah muhakkamah. The paradigm used in this research is the paradigm of literature study or document study as secondary data, namely analyzing relevant scientific theoretical reading sources so that they can be used as the basis for research analysis to solve the problems raised. This study uses analytical techniques with qualitative methods through research methods that produce analytical descriptive data, because they do not use formulas and numbers using deductive thinking methods. The results of this study are: As a basis, this rule implies that adat becomes a legal stipulation, when there are no texts. This diversity makes Indonesia a beautiful unitary state. Returning home has two impacts, namely negative and positive. On the positive side, going home can increase economic growth. On the other hand, it also has a negative impact such as demonstrations for rural communities. This will result in travelers who are more likely to be stylish and look fashionable. Basically, going home aims to be able to redistribute money in various remote areas so that economic life can continue.